2004
DOI: 10.1139/f04-072
|View full text |Cite
|
Sign up to set email alerts
|

Possible impacts of zooplankton grazing on dimethylsulfide production in the Antarctic Ocean

Abstract: The role of zooplankton grazing on dimethylsulfide (DMS) and dissolved dimethylsulfoniopropionate (DMSPd) production was investigated in the Antarctic Ocean in January and February 2002. Dominant herbivorous macrozooplankton of this region, the Antarctic krill Euphausia superba and the tunicate Salpa thompsoni, were used in shipboard incubation experiments. The concentration of DMSPd + DMS increased in the water during incubation with krill. The production rate was 2.96 ± 2.78 nmol DMSPd + DMS·krill–1·h–1 (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…The failure of menhaden phytoplanktivory to accelerate DMS formation is consistent with the sloppy feeding hypothesis for acceleration of DMS production by copepod and krill grazing. As articulated by Kasamatsu et al (2004) and others, if break-up and incomplete ingestion of phytoplankton cells during feeding are instrumental actions in the prompt acceleration of DMS production by grazing, phytoplanktivores that ingest algal cells whole would not be expected to accelerate DMS production, except possibly in long-delayed ways after feeding. Menhaden ingest cells whole according to what is known of their mode of feeding.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The failure of menhaden phytoplanktivory to accelerate DMS formation is consistent with the sloppy feeding hypothesis for acceleration of DMS production by copepod and krill grazing. As articulated by Kasamatsu et al (2004) and others, if break-up and incomplete ingestion of phytoplankton cells during feeding are instrumental actions in the prompt acceleration of DMS production by grazing, phytoplanktivores that ingest algal cells whole would not be expected to accelerate DMS production, except possibly in long-delayed ways after feeding. Menhaden ingest cells whole according to what is known of their mode of feeding.…”
Section: Discussionmentioning
confidence: 97%
“…Lee et al 2003). For example, whereas a number of laboratory studies on crustacean plankton have confirmed the finding of Dacey & Wakeham (1986) that the rate of DMS formation is increased by grazing (Daly & DiTullio 1996, Lee et al 2003, Kasamatsu et al 2004), Kwint et al (1996) found no effect. Notwithstanding variability, at present a substantial body of evidence exists that zooplankton grazing can exert major effects on the rate of DMS production, tending to increase the DMS concentration in sea surface waters and thereby force a greater flux of DMS to the atmosphere.…”
Section: Abstract: Dimethylsulfide · Dimethylsulfoniopropionate · Mementioning
confidence: 94%
See 1 more Smart Citation
“…We collected 20 different surface seawater samples from DMS hot spot sites, which matched to known DMS concentrations, from different sites during the cruise of R/V Hakuho-maru from December 2011 to March 2012 (Table 1; ) concentrations were measured by gas chromatography at the same locations where DNA samples were collected during the latter half of the cruise (at sites E1p to E2b and N3b1 to N3b2). The method was previously described in detail (28). For DMS measurement, 30 ml of seawater collected from the outlet of the shipboard built-in pumping system was directly filtered through a GF/F (47-mm) filter (Whatman, USA).…”
Section: Methodsmentioning
confidence: 99%
“…This mechanism can result in the production of DMS (Dacey and Wakeham 1986;Daly and DiTullio 1996;Kasamatsu et al 2004;Malin et al 1994). In those cases, the release of DMSP d during sloppy feeding may stimulate the conversion by algal or bacterial lyase enzymes, but microbial activity in the intestinal tract of the zooplankton and in faecal pellets may also be responsible for the high DMS production observed.…”
Section: Grazing By Meso-and Macrozooplanktonmentioning
confidence: 99%